Populist parties and democratic resilience : a cross-national analysis of populist parties' impact on democratic pluralism in Europe - Crum,Ben; Oleart, Alvaro (London ; New York : Routledge, 2023)
"Populist Parties and Democratic Resilience focuses on populist parties as the main agents of populism and examines when these parties turn anti-democratic and when they remain loyal to the democratic system. Following the Brexit referendum, the election of Donald Trump, and the rise of populist parties around the globe, many observers suggested that democracy was in serious trouble. Nevertheless, while some democratic systems have been seized by populists, most of them have proven resilient. In this volume, the authors identify the conditions under which populist parties become inimical to political and societal pluralism. They offer in-depth analyses of the trajectory of populist parties in eleven European Union countries (Austria, Belgium, Czech Republic, France, Germany, Hungary, Italy, The Netherlands, Poland, Romania, and Spain). The book shows that, reflecting the diversity of national contexts, there are multiple pathways whereby populist parties' power can remain contained and subject to democratic checks and balances. Moreover, populist parties can - at times voluntarily, at other times by force of external conditions - come to adhere to the democratic rules of the game. On this basis, the volume outlines different ways in which European democracies can successfully accommodate populist parties through strategies that carefully navigate between the extremes of uncritical acceptance and outright ostracization. Drawing on the literature on democratic theory and comparative politics, this book directly contributes to the public debate on the state of democracy in Europe. It will be of interest to researchers of comparative politics, European politics, party politics, democracy, and populism"--
Introduction: Populist Parties, Pluralism and Democratic Systems in Europe -- Varieties of Populism in East-Central Europe: From Democratic Challenge to Illiberal Project -- Explaining Democratic Backsliding in Poland: The Interplay of Party-specific and Contextual Factors -- Anti-pluralist Reactions to an Anti-pluralist Party: The 'Alternative for Germany' and the German Party System -- Making a Wor(l)d of Difference? The National Front's Anti-pluralist Stands and their Evolution Over Time -- Protector of the People or Enemy of Democracy? Vlaams Belang's Anti-pluralist Discourse and Institutional Barriers in the Flemish Political System -- Party System Hospitality, Internal Strife, and Radicalisation: The Evolution of the Partij voor de Vrijheid and the Forum voor Democratie in the Netherlands -- Taming Populist Anti-pluralism? The Effect of Changing Centre-right Strategies on the Austrian Freedom Party -- The Five Star Movement and its Challenge to the Pluralistic Foundations of Italian Democracy -- The Conditioning of Podemos by Mainstream PSOE between 2014 and 2020: From Transformative Populism to Mainstream Centre-left Coalition Partner -- Conclusion: How to Channel Populism in Europe Democratically.
Includes bibliographical references and index.
Keywords: Political parties -- European Union countries; Populism -- European Union countries; Right and left (Political science) -- European Union countries; Pluralism -- Political aspects; European Union countries -- Politics and government -- 21st century